THE POTENTIAL OF CLOUD SERVICES FOR BUILDING INFORMATION SECURITY COMPETENCES IN PRE-SERVICE TEACHER EDUCATION - Ihnatenko В. О. (Journal of Information Technologies in Education (ITE), 2025)
The article examines modern information technologies in the context of information security, reveals the potential of cloud technologies as a key element of digitalisation of modern education and the possibilities of their use in the professional training of future teachers. In the context of the constant development and transformation of the educational space and the information society, cloud technologies are an effective tool that helps to form digital, information and communication, and information security competencies. The article analyses the main advantages of using cloud technologies, among which the personalisation of the educational process, expansion of opportunities for distance and blended education, instant exchange of educational materials, and creation of an interactive educational environment are particularly noteworthy. The article pays special attention to the issue of information security of future teachers, noting that a modern teacher should be aware of the methods of identifying information threats, have the skills to use digital resources safely and create an information-secure learning environment. The necessity of integrating information security competencies into the educational standards for teacher training is substantiated. The article contains an analysis of a number of current challenges related to the introduction of cloud services into educational practice, including technical barriers, lack of common standards, insufficient digital literacy of teachers, and regulatory issues. Overcoming these obstacles is a prerequisite for the effective implementation of cloud technologies in pedagogical activities. The conclusions emphasise the importance of using cloud technologies to upgrade the infrastructure of educational institutions, to form digital culture, critical thinking, media literacy, and digital responsibility of future teachers, which ensures their competitiveness in the dynamic information space.